Effects of velocity loss during resistance training on athletic performance, strength gains and muscle adaptations - Pareja‐Blanco, F.; Rodríguez‐Rosell, D.; Sánchez‐Medina, L.; Sanchis‐Moysi, J.; Dorado, C.; Mora‐Custodio, R.; Yáñez‐García, J. M.; Morales‐Alamo, D.; Pérez‐Suárez, I.; Calbet, J. A. L.; González‐Badillo, J. J. (Scandinavian journal of medicine & science in sports, 2017)
We compared the effects of two resistance training (RT) programs only differing in the repetition velocity loss allowed in each set: 20% (VL20) vs 40% (VL40) on muscle structural and functional adaptations. Twenty‐two young males were randomly assigned to a VL20 (n = 12) or VL40 (n = 10) group. Subjects followed an 8‐week velocity‐based RT program using the squat exercise while monitoring repetition velocity. Pre‐ and post‐training assessments included: magnetic resonance imaging, vastus lateralis biopsies for muscle cross‐sectional area (CSA) and fiber type analyses, one‐repetition maximum strength and full load‐velocity squat profile, countermovement jump (CMJ), and 20‐m sprint running. VL20 resulted in similar squat strength gains than VL40 and greater improvements in CMJ (9.5% vs 3.5%, P < 0.05), despite VL20 performing 40% fewer repetitions. Although both groups increased mean fiber CSA and whole quadriceps muscle volume, VL40 training elicited a greater hypertrophy of vastus lateralis and intermedius than VL20. Training resulted in a reduction of myosin heavy chain IIX percentage in VL40, whereas it was preserved in VL20. In conclusion, the progressive accumulation of muscle fatigue as indicated by a more pronounced repetition velocity loss appears as an important variable in the configuration of the resistance exercise stimulus as it influences functional and structural neuromuscular adaptations.